(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Climate change has emerged as a significant threat to global agriculture, particularly in semi-arid regions. This research paper investigates the impact of climate change on agricultural productivity in two key regions of Maharashtra, India—Marathwada and Vidarbha. Both regions have experienced fluctuations in temperature, erratic rainfall, and an increase in extreme weather events over recent decades. These changes have had profound implications for agricultural productivity, affecting crop yield, farmer livelihoods, and food security. The study aims to compare and contrast the effects of climate change on the agricultural productivity of these two regions using meteorological data, crop productivity trends, and field interviews with farmers. The findings reveal that while both regions are severely affected, differences in crop patterns, water resource management, and policy responses have led to varying levels of resilience and adaptation. The paper concludes by suggesting targeted climate adaptation strategies to mitigate the adverse effects on agriculture in both regions.